CONCEPCIONES DEL ALMA, EL CUERPO Y EL INTELECTO EN IBN ḤAZM DE CÓRDOBA. - Quintana, Pablo (Revista Española de Filosofía Medieval, 2024)
This article presents an analysis of the arguments that Ibn Ḥazm of Córdoba exposes, mainly in his Kitāb al-Fiṣal, in order to refute a set of ideas attributed to the "Ancients" which refer to the nature and faculties of the soul, and its relationship to the body and the intellect. His treatment of the soul is not systematic nor are his considerations exposed through direct references to the Greek philosophical tradition or the falāsifa as the basis of his doctrine. Therefore, we will focus on the identification of the philosophical principles that underlie both the arguments that Ibn Ḥazm intends to refute and his own doctrine about the soul.